Mast cell activation tests by flow cytometry: A new diagnostic asset?. Issue 11 (18th July 2021) - Elst, Jessy; van der Poorten, Marie‐Line M.; Van Gasse, Athina L.; De Puysseleyr, Leander; Hagendorens, Margo M.; Faber, Margaretha A.; Van Houdt, Michel; Passante, Egle; Bahri, Rajia; Walschot, Mark; Mertens, Christel; Bridts, Chris H.; et al.
Abstract: Since the late nineties, evidence has accumulated that flow‐assisted basophil activation test (BAT) might be an accessible and reliable method to explore the mechanisms governing basophil degranulation and diagnostic allowing correct prediction of the clinical outcome following exposure to the offending allergen(s) and cross‐reactive structures for different IgE‐dependent allergies and particular forms of autoimmune urticaria. Although the BAT offers many advantages over mediator release tests, it is left with some weaknesses that hinder a wider application. It is preferable to perform the BAT analysis within 4 h of collection, and the technique does not advance diagnosis in patients with non‐responsive cells. Besides, the BAT is difficult to standardize mainly because of the difficulty to perform large batch analyses that might span over several days. This article reviews the status of flow cytometric mast cell activation test (MAT) using passively sensitized mast cells (MCs) with patients' sera or plasma (henceforth indicated as passive MAT; pMAT) using both MC lines and cultured MCs in the diagnosis of IgE‐dependent allergies. In addition, this paper provides guidance for generating human MCs from peripheral blood CD34 + progenitor cells (PBCMCs) and correct interpretation of flow cytometric analyses of activated and/or degranulating cells. With the recent recognition of the mas‐related G protein‐coupled receptor X2 (MRGPRX2) occupation as a putative mechanism of immediate drug hypersensitivity reactions (IDHRs), we also speculate how direct activation of MCs (dMAT)—that is direct activation by MRGPRX2 agonists without prior passive sensitization—could advance paradigms for this novel endotype of IDHRs. Abstract : The passive mast cell activation test (MAT), which uses mast cells (MCs) that were passively sensitized with patients' sera, is a promising diagnostic for IgE‐mediated allergies. For autoimmune urticaria, in the autoimmune MAT, MCs can directly be activated with patients' sera or after passive sensitization with donor IgE. Besides, the MCs can directly be activated through MRGPRX2 with simultaneous analysis of the MRGPRX2 + and MRGPRX2 − subpopulations. MC degranulation can be studied via up‐regulation of specific degranulation markers or mediator release.